Convective heat transfer in square and cylindrical porous annulus / Salman Ahamed Khan Jagirdar - Salman Ahamed Khan , Jagirdar (2013)
The convective heat transfer in porous media has attracted the considerable attention in the past few decades due to its wide applicability in various fields. The present work focuses on investigating the various aspects of convection such as conjugate heat transfer, conjugate double diffusion and mixed convection analysis with thermal equilibrium and thermal non-equilibrium modeling. The finite element method is used to discretize the governing non-linear partial differential equations. Galerkins method has been employed to accomplish the element stiffness matrix. An in-house computer code was developed to solve the resulting equations that describe the behavior of heat transfer in porous medium. The various geometrical and physical parameters have been analyzed with respect to the porous annular duct and annular cylinders embedded with saturated porous medium. The effects of Rayleigh number, radiation parameter, thermal conductivity ratio, Peclet number, duct thickness ratio and other characteristics have been evaluated to determine the variation in the Nusselt number and fluid flow behavior. It has been found that the fluid flow in the considered geometry, exhibit various types of movement due to the enhancement or retardation in the temperature at the vicinity of the solid wall of the annulus. It has also been found that the fluid moves in two symmetric cells due to the isothermal heating and cooling of outer and inner walls of the respective ducts.